Analisis Kritis dan Upaya Pengembangan Layanan Konseling Cyber dalam Perspektif Komunikasi dan Dakwah - Puandina, Ana Bella; Nurjannah (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
Social media has influenced how individuals live their lives nowadays and can help with the introduction of cybertherapy. To help people overcome their issues and grow as individuals, counsellors may provide them with "cyber counselling," which is an aid provided by using the internet to communicate with clients. Using technology like cyber counselling will simplify offering counselling services at any time and from any location. Although it provides several advantages, implementing cyber counselling services still has many things that could be improved. It is a scientific activity that benefits the advancement of science when contemporary researchers critique and develop earlier scientific beliefs. For the counselling process to function well and produce the best outcomes possible for helping customers cope with their difficulties, this research aims to penalise online counselling services and provide development options that may be helpful. A literature review or study is the sort of research being conducted here. So that this cyber counselling service can be developed, Islamic elements are added with a focus on the skills of Islamic counsellors in providing cyber counselling services.